Enantioselective alkylation of aromatic aldehydes with (+)-camphoric acid derived chiral 1, 3-diamine ligands. Issue 2 (15th February 2017) - Serra, M. Elisa Silva; Murtinho, Dina; Paz, Victória
Graphical abstract: Chiral camphoric acid derived 1, 3-diamines were prepared and tested in the enantioselective alkylation of benzaldehyde with diethylzinc, giving products with er up to 86:14. The most selective ligand was tested in the alkylation of other aromatic aldehydes originating product alcohols with er up to 93.5:6.5 in 2 h with 5 mol % ligand. Abstract: A series of chiral 1, 3-diamine ligands derived from (+)-camphoric acid were prepared from the reaction of 1, 3-diamino-1, 2, 2-trimethylcyclopentane with aromatic aldehydes, followed by reduction of the corresponding diimines. These newly synthesized ligands were tested in the enantioselective alkylation of benzaldehyde with diethylzinc, giving 1-phenyl-1-propanol with enantiomeric ratios of up to 86:14. Our most selective ligand, derived from 2-methoxybenzaldehyde, was also tested in the alkylation of several aromatic aldehydes and product alcohols with enantiomeric ratios of up to 93.5:6.5 being observed in 2 h at room temperature in the presence of 5 mol % ligand. Abstract : (1 R, 3 S )- N, N ′-Bis[phenylidene]-1, 3-diamino-1, 2, 2-trimethylcyclopentane: C22 H26 N2 Ee = 100% [ α ] D 20  = +36.2 ( c 1, CH2 Cl2 ) Source of chirality: (+)-camphoric acid Absolute configuration: (1 R, 3 S ) Abstract : (1 R, 3 S )- N, N ′-Bis[2-methoxyphenylidene]-1, 3-diamino-1, 2, 2-trimethylcyclopentane: C24 H30 N2 O2 Ee = 100% [ α ] D 20  = -1.7 ( c 6, CH2 Cl2 ) Source of chirality: (+)-camphoric acid Absolute configuration: (1 R, 3 S ) Abstract : (1 R, 3 S )- N, N ′-Bis[2-methylphenylidene]-1, 3-diamino-1, 2, 2-trimethylcyclopentane: C24 H30 N2 Ee = 100% [ α ] D 20  = +29.7 ( c 1, CH2 Cl2 ) Source of chirality: (+)-camphoric acid Absolute configuration: (1 R, 3 S ) Abstract : (1 R, 3 S )- N, N ′-Bis[2-chlorophenylidene]-1, 3-diamino-1, 2, 2-trimethylcyclopentane: C22 H24 Cl2 N2 Ee = 100% [ α ] D 20  = +7.2 ( c 2.1, CH2 Cl2 ) Source of chirality: (+)-camphoric acid Absolute configuration: (1 R, 3 S ) Abstract : (1 R, 3 S )- N, N ′-Bis[3-methoxyphenylidene]-1, 3-diamino-1, 2, 2-trimethylcyclopentane: C24 H30 N2 O2 Ee = 100% [ α ] D 20  = +45.0 ( c 1, CH2 Cl2 ) Source of chirality: (+)-camphoric acid Absolute configuration: (1 R, 3 S ) Abstract : (1 R, 3 S )- N, N ′-Bis[4-methoxyphenylidene]-1, 3-diamino-1, 2, 2-trimethylcyclopentane: C24 H30 N2 O2 Ee = 100% [ α ] D 20  = +45.0 ( c 1, CH2 Cl2 ) Source of chirality: (+)-camphoric acid Absolute configuration: (1 R, 3 S ) Abstract : (1 R, 3 S )- N, N ′-Bis[2, 6-dichlorophenylidene]-1, 3-diamino-1, 2, 2-trimethylcyclopentane: C22 H22 Cl4 N2 Ee = 100% [ α ] D 20  = +4.0 ( c 5, CH2 Cl2 ) Source of chirality: (+)-camphoric acid Absolute configuration: (1 R, 3 S ) Abstract : (1 R, 3 S )- N, N ′-Bis[2, 4, 6-trimethylphenylidene]-1, 3-diamino-1, 2, 2-trimethylcyclopentane: C28 H38 N2 Ee = 100% [ α ] D 20  = +25.0 ( c 1, CH2 Cl2 ) Source of chirality: (+)-camphoric acid Absolute configuration: (1 R, 3 S ) Abstract : (1 R, 3 S )- N, N ′-Bis[1-phenylmethyl]-1, 3-diamino-1, 2, 2-trimethylcyclopentane: C22 H30 N2 Ee = 100% [ α ] D 20  = +47.8 ( c 1.2, CH2 Cl2 ) Source of chirality: (+)-camphoric acid Absolute configuration: (1 R, 3 S ) Abstract : (1 R, 3 S )- N, N ′-Bis[1-(2-methoxyphenyl)methyl]-1, 3-diamino-1, 2, 2-trimethylcyclopentane: C24 H34 N2 O2 Ee = 100% [ α ] D 20  = +39.4 ( c 1, CH2 Cl2 ) Source of chirality: (+)-camphoric acid Absolute configuration: (1 R, 3 S ) Abstract : (1 R, 3 S )- N, N ′-Bis[1-(2-methylphenyl)methyl]-1, 3-diamino-1, 2, 2-trimethylcyclopentane: C24 H34 N2 Ee = 100% [ α ] D 20  = +44.9 ( c 1.2, CH2 Cl2 ) Source of chirality: (+)-camphoric acid Absolute configuration: (1 R, 3 S ) Abstract : (1 R, 3 S )- N, N ′-Bis[1-(2-chlorophenyl)methyl]-1, 3-diamino-1, 2, 2-trimethylcyclopentane: C24 H28 Cl2 N2 Ee = 100% [ α ] D 20  = +37.0 ( c 1.1, CH2 Cl2 ) Source of chirality: (+)-camphoric acid Absolute configuration: (1 R, 3 S ) Abstract : (1 R, 3 S )- N, N ′-Bis[1-(3-methoxyphenyl)methyl]-1, 3-diamino-1, 2, 2-trimethylcyclopentane: C24 H34 N2 O2 Ee = 100% [ α ] D 20  = +43.5 ( c 1.2, CH2 Cl2 ) Source of chirality: (+)-camphoric acid Absolute configuration: (1 R, 3 S ) Abstract : (1 R, 3 S )- N, N ′-Bis[1-(4-methoxyphenyl)methyl]-1, 3-diamino-1, 2, 2-trimethylcyclopentane: C24 H34 N2 O2 Ee = 100% [ α ] D 20  = +40.0 ( c 1.1, CH2 Cl2 ) Source of chirality: (+)-camphoric acid Absolute configuration: (1 R, 3 S ) Abstract : (1 R, 3 S )- N, N ′-Bis[1-(2, 6-dichlorophenyl)methyl]-1, 3-diamino-1, 2, 2-trimethylcyclopentane: C22 H26 Cl4 N2 Ee = 100% [ α ] D 20  = +30.0 ( c 1, CH2 Cl2 ) Source of chirality: (+)-camphoric acid Absolute configuration: (1 R, 3 S ) Abstract : (1 R, 3 S )- N, N ′-Bis[1-(2, 4, 6-trimethylphenyl)methyl]-1, 3-diamino-1, 2, 2-trimethylcyclopentane: C28 H42 N2 Ee = 100% [ α ] D 20  = +34.1 ( c 1, CH2 Cl2 ) Source of chirality: (+)-camphoric acid Absolute configuration: (1 R, 3 S )